Multiple Regional Listing Increases Liver Transplant Rates for Those With Model for End-stage Liver Disease Score <15. Issue 4 (April 2020) - Brown, Sara; Savva, Yulia; Barth, Rolf; LaMattina, John; Thuluvath, Paul J.
Abstract : Background: Multiple listing (ML) at >1 transplant center is one mechanism to combat the geographic disparities in liver transplantation (LT) rates. The objective of our study was to determine the impact of multiple listing on LT rates. Methods: We examined the United Network of Organ Sharing database from 2002 to 2016 after excluding those listed for multiple organs, hepatocellular carcinoma, or living donor LT. The waitlist mortality and LT rates for the ML groups and the single listed (SL) group were compared after stratifying patients by the Model for End-Stage Liver Disease (MELD) with a cutoff at 15 (<15 and ≥15). Results: Of the 83 935 listed during the study period, 80 351 were listed in a single center (SL group), and 3584 were listed in >1 center (ML group). Of the ML groups, 2028 (2.4%) were listed at multiple donor service areas but within the same region (ML-SR) and 1556 (1.9%) listed in different regions (ML-DR). The median MELD at LT was 20, 21, and 24 for ML-DR, ML-SR, and SL groups, respectively ( P = 0.001). Although the probability of receiving LT was significantly higher for the ML groups relative to the SL group for both MELD groups (<15 and ≥15), the impact was the highest for ML-DR group. At MELD score <15, the probability of LT was 72% for ML-DR, 38% for ML-SR, and 32% for SL groups. At MELD score ≥15, the probability of LT was 79% for ML-DR, 67% for ML-SR, and 61% for SL groups. Conclusions: Multiple listing appeared to considerably improve a patient's chance of receiving LT and survival with the highest benefit for those with low MELD scores (<15) listed at multiple regions. Abstract : Supplemental Digital Content is available in the text.